DIGITAL STORYTELLING IN ENGLISH LANGUAGE LEARNING: EFFECTS ON SPEAKING FLUENCY, NARRATIVE COMPETENCE, AND STUDENTS' ENGAGEMENT - Zaki Al Fuad; Helminsyah Helminsyah (Sensei International Journal of Education and Linguistic, 2023)
Speaking instruction in English as a foreign language classrooms often provides insufficient opportunities for sustained oral production, narrative organization, rehearsal, and audience-oriented communication. Digital storytelling combines spoken narration with images, text, music, and video, potentially creating a meaningful environment for developing oral language and multimodal communication. This study examined the effects of digital storytelling on students' speaking fluency, narrative competence, and classroom engagement. A mixed-method quasi-experimental design involved 88 tenth-grade students assigned to an experimental group and a control group. The experimental group completed an eight-session digital storytelling project involving story mapping, script development, oral rehearsal, multimedia production, peer feedback, revision, and public presentation. The control group received conventional spoken-narrative instruction using textbook modelling, individual practice, and classroom presentation. Data were collected through speaking performance tests, narrative competence rubrics, engagement questionnaires, observations, interviews, reflective journals, and digital story artifacts. Quantitative data were analyzed using descriptive statistics, paired-sample and independent-sample t-tests, normalized gain, and effect size. Qualitative data were analyzed thematically. The experimental group significantly outperformed the control group in speaking performance, narrative competence, and engagement. Improvements were strongest in fluency, narrative sequencing, audience awareness, and social engagement. The study concludes that digital storytelling can strengthen oral English learning when multimedia production is integrated with explicit narrative instruction, repeated rehearsal, formative feedback, and equitable access to digital tools.